Preconsultation Educational Group Intervention Can Address the Knowledge Gap in Postmastectomy Breast Reconstruction. Issue 6 (June 2021) - Zhong, Toni; Quong, Whitney L.; Cheng, Terry; Kerrebijn, Isabel; Butler, Kate; Hofer, Stefan O. P.; O'Neill, Anne C.; Cil, Tulin D.; Metcalfe, Kelly A.
Abstract : Background: Whether to undergo postmastectomy breast reconstruction (PMBR) is a challenging, preference-sensitive decision. It is therefore paramount to optimize decision quality through ensuring patients' knowledge and aligning treatments with their personal preferences. This study assessed the effects of a preconsultation educational group intervention (PEGI) on patient knowledge, state-trait anxiety, and decisional conflict (patient uncertainty in decision making) during the decision-making process. Methods: This phase 3 randomized controlled trial assessed effects of a PEGI in women without active breast cancer undergoing delayed PMBR, or prophylactic mastectomy with immediate PMBR. Both groups underwent routine education before consultation. In addition, the intervention group underwent a PEGI composed of presentations from a plastic surgeon and nurse, a value clarification exercise, and shared experiences from PMBR patients before the consultation with the plastic surgeon. Before and 1-week after consultation, outcome measures were assessed using the Decisional Conflict Scale, State-Trait Anxiety Inventory, and the BREAST-Q. Results: Of the 219 women deemed eligible, a total of 156 women were recruited and randomized. Treatment fidelity was 96% and retention was 88%. At baseline, there were no significant differences in terms of demographic or clinical status, knowledge, state-trait anxiety, and decisional conflict. Patient knowledge about PMBR improved in both groups; however, the degree of knowledge attainment was significantly greater in the PEGI group (24.5% improvement in the intervention group compared with 13.5% in the routine education group, P < 0.001). The reduction in decisional conflict from baseline to follow-up was greater in the intervention group compared with the routine education; however, the difference only approached significance ( P = 0.09). Conclusions: The provision of a preconsultation educational group intervention has been shown to significantly close the knowledge gap on PMBR in patients seeking delayed breast reconstruction or prophylactic mastectomy with immediate breast reconstruction compared with routine education alone.